Endogenous Stem Cell-Based In Situ Tissue Regeneration Using Electrostatically Interactive Hydrogel with a Newly Discovered Substance P Analog and VEGF-Mimicking Peptide - Park, Seung Hun; Ju, Hyeon Jin; Ji, Yun Bae; Shah, Masaud; Min, Byoung Hyun; Choi, Hak Soo; Choi, Sangdun; Kim, Moon Suk (Small, 2021)
The use of chemoattractants to promote endogenous stem cell-based in situ tissue regeneration has recently garnered much attention. This study is the first to assess the endogenous stem cell migration using a newly discovered substance P (SP) analog (SP1) by molecular dynamics simulations as an efficient chemoattractant. Further, a novel strategy based on electrostatic interaction using cationic chitosan (Ch) and anionic hyaluronic acid (HA) to prepare an SP1-loaded injectable C/H formulation without SP1 loss is developed. The formulation quickly forms an SP1-loaded C/H hydrogel in situ through in vivo injection. The newly discovered SP1 is found to possess human mesenchymal stromal cells (hMSCs) migration-inducing ability that is approximately two to three times higher than that of the existing SP. The designed VEGF-mimicking peptide (VP) chemically reacts with the hydrogel (C/H-VP) to sustain the release of VP, thus inducing vasculogenic differentiation of the hMSCs that migrate toward the C/H-VP hydrogel. Similarly, in animal experiments, SP1 attracts a large number of hMSCs toward the C/H-VP hydrogel, after which VP induces vasculogenic differentiation. Collectively, these findings indicate that SP1-loaded C/H-VP hydrogels are a promising strategy to facilitate endogenous stem cell-based in situ tissue regeneration.
Keywords: Animal experiments; Cationic chitosans; Chemoattractants; Endogenous stem cells; Mesenchymal stromal cells; Molecular dynamics simulations; Novel strategies; Vasculogenic; Animals; Humans; Hyaluronic Acid; Hydrogels; Mesenchymal Stem Cells; Stem Cells; Substance P; Vascular Endothelial Growth Factor A; chemoattractants; differentiation; endogenous stem cells; hydrogels; in situ tissue regeneration; migration